1978
DOI: 10.1002/j.1839-4655.1978.tb00619.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Suicide in an Australian Metropolis: The Case of Sydney

Abstract: The ecological patterns of suicide in metropolitan Sydney are described and policy recommendations made. Some inferences about the association of urbanization with suicide are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…This pattern was generally similar to those shown in a number of Western cities (Buglass and Duffy, 1978;Burnley, 1978;Cavan, 1928;Congdon, 1996a;Gunnell et al, 2012;Middleton et al, 2008). By contrast, a few studies investigating the spatial distribution of suicide in non-Western world showed somewhat different patterns.…”
Section: Spatial Patterning Of Suicidesupporting
confidence: 67%
See 1 more Smart Citation
“…This pattern was generally similar to those shown in a number of Western cities (Buglass and Duffy, 1978;Burnley, 1978;Cavan, 1928;Congdon, 1996a;Gunnell et al, 2012;Middleton et al, 2008). By contrast, a few studies investigating the spatial distribution of suicide in non-Western world showed somewhat different patterns.…”
Section: Spatial Patterning Of Suicidesupporting
confidence: 67%
“…However, past research into the spatial distribution of suicide in urban areas has mostly been restricted to cities of developed Western nations. Previous studies showed that high suicide rates tend to cluster in inner city areas in Western cities, such as Chicago (Cavan, 1928), Edinburgh (Buglass and Duffy, 1978), Sydney (Burnley, 1978), and London (Congdon, 1996a;Gunnell et al, 2012;Middleton et al, 2008). In contrast, little is known about geographic variations in suicide in non-Western cities.…”
Section: Introductionmentioning
confidence: 83%
“…Dating back to Learmonth's work in the sixties, heart diseases, stroke and cancer have featured prominently in the geography of health literature. Ischaemic heart disease was portrayed at a national scale (McGlashan, 1977) and heart disease and stroke within Sydney (Burnley, 1977). More recently, in a compendium of worldwide patterns of cancer (Howe, 1986), McGlashan and Baghurst (1986) have employed statistical means to demonstrate significant variations across the nation of death from the three major cancers of each sex (see Table 1).…”
Section: Geographical Pathology In Australiamentioning
confidence: 99%
“…This reflects the only partial adequacy of census-derived indicators as independent variables in multivariate analyses and also a random element in the high and low incidence of mortality or morbidity by area, particularly in the situation of such small base populations as occur in non-metropolitan areas of Australia. Mortality analyses have also been undertaken at the intra-metropolitan level, and it has been shown that significant spatial variations occur in infant mortality (Burnley, 1977). suicide (Burnley, 1978), heart disease and cancer (Burnley, 1980) and total mortality.…”
Section: Mortality Studiesmentioning
confidence: 99%